Implementasi Pendekatan Saintifik pada Pembelajaran Tematik Terpadu di Kelas IV MIN 1 Yogyakarta - Muhammad Asrofi; Desiana Wahyuni (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2019)
This study aims to find out how the implementation of the scientific approach to integrated thematic learning in class IV MIN 1 Yogyakarta, which includes planning, implementation, assessment, obstacles, and efforts to overcome. This study is a type of qualitative research. The subjects of this study are the Head of MIN 1 Yogyakarta, teachers and students in class IV. Data collection in this study is carried out by the method of observation, interviews, documentation, and questionnaires. Data analysis uses data triangulation and conclusion drawing. The results show that the teachers have compiled the lesson plan outlining the steps of the activity with a scientific approach. The teachers have implemented learning using a scientific approach but the implementation has not been maximized. Teachers also do not use authentic assessment to the fullest. Teachers rarely use instruments and assessment rubrics. Barriers experienced by teachers in implementing scientific approaches include obstacles in planning, implementing, and evaluating learning. Keywords: implementation, scientific approach, integrated thematic learning